2009
DOI: 10.1104/pp.108.131524
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Response of Pea Plants to Cadmium Toxicity: Cross Talk between Reactive Oxygen Species, Nitric Oxide, and Calcium    

Abstract: Cadmium (Cd) toxicity has been widely studied in different plant species; however, the mechanism involved in its toxicity as well as the cell response against the metal have not been well established. In this work, using pea (Pisum sativum) plants, we studied the effect of Cd on antioxidants, reactive oxygen species (ROS), and nitric oxide (NO) metabolism of leaves using different cellular, molecular, and biochemical approaches. The growth of pea plants with 50 mM CdCl 2 affected differentially the expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

28
289
4
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 560 publications
(323 citation statements)
references
References 122 publications
28
289
4
2
Order By: Relevance
“…Obviously, accumulation of As had more inhibitory effect on the roots of present P. vulgaris seedlings than on the shoots, agreeing well with earlier reports (Uchida et al 2002;Ahmed et al 2006;Talukdar 2011a). Heavy metal-induced structural changes in the plant parts were also reported in mung bean ), pea (Rodríguez-Serrano et al 2009) and in Fig. 2 Cross-section of root in (a) control, (b) 50 μM As showing absence of hair, disintegration of vascular bundles (thin arrow) and loosening of cells (thick arrow), (c) As + SNP-supplemented media showing root hair (thin arrow) and thickening of epidermal layer (thick arrow) and (d) in AS + PTIO media exhibiting completely disorganized cortex and vascular bundles (→).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Obviously, accumulation of As had more inhibitory effect on the roots of present P. vulgaris seedlings than on the shoots, agreeing well with earlier reports (Uchida et al 2002;Ahmed et al 2006;Talukdar 2011a). Heavy metal-induced structural changes in the plant parts were also reported in mung bean ), pea (Rodríguez-Serrano et al 2009) and in Fig. 2 Cross-section of root in (a) control, (b) 50 μM As showing absence of hair, disintegration of vascular bundles (thin arrow) and loosening of cells (thick arrow), (c) As + SNP-supplemented media showing root hair (thin arrow) and thickening of epidermal layer (thick arrow) and (d) in AS + PTIO media exhibiting completely disorganized cortex and vascular bundles (→).…”
Section: Discussionmentioning
confidence: 73%
“…NO-mediated inhibition of both CAT and APX was explained as a redox signaling process during the activation of defense against pathogen attack in tobacco (Clark et al 2000). Several studies pointed out role of H 2 O 2 as a signal molecule in defense cross-talk with NO during response to abiotic stresses (Neill et al 2002;Singh et al 2007;Rodríguez-Serrano et al 2009). Significant increase in root POX level, as observed in this study, might be responsible for cell wall thickness in SNP + As-treated roots.…”
Section: Discussionmentioning
confidence: 99%
“…The stress conditions that increase plant annexin abundance and recruitment to membranes (e.g. exogenous abscisic acid, drought, salinity, metal stress [Bianchi et al, 2002;Repetto et al, 2003;Lee et al, 2004;Vandeputte et al, 2007;Konopka-Postupolska et al, 2009]) can also result in ROS production (Demidchik et al, 2003;Boudsocq and Laurière, 2005;Konopka-Postupolska et al, 2009;Rodríguez-Serrano et al, 2009) and the lipid peroxidation that is typified by increases in MDA content (Demiral and Turkan, 2005;Collin et al, 2008). This suggests that annexins could function in integrating ROS and Ca 2+ in stress signaling.…”
Section: Consequences For Ros-and Ca 2+ -Based Signalingmentioning
confidence: 99%
“…[4][5][6][7][8][9] Recent research has revealed that metal-mediated stress seems to have a direct impact on accumulation of relative oxygen species (ROS), content of nitric oxide (NO) and hormone levels in organs and the plants can quickly adjust their growth to harsh environment by influencing the cellular redox state and hormone signaling. [10][11][12][13][14][15][16] This review provides an update on the regulation of plant responses to metal-stress by ROS and auxin signaling pathway, primarily, with a focus on the copper, aluminum and cadmium stress. The mechanisms underlying how metal stress modulates the changes in auxin distribution and the network of ROS and auxin in plant response to metal stress are discussed based on recent studies.…”
mentioning
confidence: 99%